Proposal of a protocol for pelvic floor muscle evaluation and training to provide care to women with urinary incontinence - Gisela Maria Assis; Camilla Pinheiro Cristaldi da Silva; Gisele Martins (SciELO, 2021)
ABSTRACT Objective: To present a proposal of a protocol for pelvic floor muscle evaluation and training to provide care to women with urinary incontinence. Method: Professional experience report, conducted in an outpatient facility for voiding dysfunctions in the Brazilian Unified Health System, conducted by an enterostomal therapist nurse. Results: Elaboration of a proposal of care protocol in nursing consultations based on a directed physical examination, nursing diagnoses of the International Classification for Nursing Practice, and the adaptation of a muscle training protocol as prescription. Steps: static observation, dynamic observation, and palpation to verify the tension and evaluation of strength, sustentation, relaxation, and muscle coordination, followed by prescriptions for relaxation, proprioception, training for strength, sustentation, abdominal and pelvic coordination, and maintenance, as per diagnosis. Conclusion: This protocol proposal intends to support the evaluation of the pelvic muscles of women with urinary incontinence or at risk for developing this condition by nurses of all levels of healthcare, especially as part of nursing consultations in primary care.